Clinician–Educators as Dual Professionals: A Contemporary Reappraisal. (July 2016) - Stoddard, Hugh A.; Brownfield, Erica D.
Abstract : Physicians who teach face unique responsibilities and expectations because they must educate learners while simultaneously caring for patients. Recently this has become even more difficult as the environment for clinician–educators has been undermined by public antipathy toward both the education profession and the medicine profession. Erosion of public confidence in both professions is evidenced by three trends. First, the democratizing nature of the Internet and the availability of technical knowledge to laypeople have encroached on the domain of professional knowledge. Second, the responsibility of a professional to make decisions has been undercut by legal interpretations regarding how physicians are paid for patient care and how teachers are evaluated on performance. And finally, altruistic motivations in both professions have been called into question by external forces promoting "accountability" rather than trusting professionals to act for the best interest of their patients or students. In this climate of increasing accountability and decreasing trust for professionals, clinician–educators can best serve patients and learners through transdisciplinary collaboration with professional educators. Clinician–educators should rely on professional educators for judgment and specialized knowledge in the field of education rather than embodying both professions by themselves. Health care practice has become more team oriented; health care education should do likewise to counteract the social and political trends eroding public confidence in medicine and education. Relying on collaboration with education professionals constitutes a substantial change to how clinician–educators define themselves, but it holds the best promise for medical training in the current social milieu.